2019
DOI: 10.1111/jfbc.13131
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacological studies on the efficacy of a thymoquinone‐containing novel polyherbal formulation against cisplatin‐induced hepatorenal toxicity in rats

Abstract: The aim of this study was to investigate the protective effect of a novel polyherbal formulation against cisplatin-induced hepatorenal toxicity in six groups of rats. Group I: Normal control; Group II: cisplatin (5 mg/kg i.p.); Group III: cisplatin (5 mg/kg i.p.) + cystone (750 mg/kg p.o.); Group IV: cisplatin + Costus speciosus, Fumaria indica, Cichorium intybus, and thymoquinone (CFCT) (25 mg/kg p.o.); Group V: cisplatin + CFCT-50; Group VI: cisplatin + CFCT-100. The rats were treated for 4 weeks. Serum and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
15
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 43 publications
(54 reference statements)
2
15
0
Order By: Relevance
“…The histological and immunohistochemical observations of the current study are in harmony and confirmed the alterations of the biochemical and oxidant/antioxidant parameters among the experimental groups. Several histological changes in the liver among CP treated group were noted as recently mentioned by Abuzinadah and Ahmad (2020). The central vein and sinusoidal dilatation and congestion are in accordance with Cagin et al (2015) and Omar et al (2016).…”
Section: Discussionsupporting
confidence: 74%
See 4 more Smart Citations
“…The histological and immunohistochemical observations of the current study are in harmony and confirmed the alterations of the biochemical and oxidant/antioxidant parameters among the experimental groups. Several histological changes in the liver among CP treated group were noted as recently mentioned by Abuzinadah and Ahmad (2020). The central vein and sinusoidal dilatation and congestion are in accordance with Cagin et al (2015) and Omar et al (2016).…”
Section: Discussionsupporting
confidence: 74%
“…Cisplatin administration produced a significant decrease in the total proteins and albumin, this result is supported by the result of Abuzinadah and Ahmad (2020) . The above-mentioned results indicate disturbances in protein metabolism induced by CP intoxication due to a reduction in protein synthesis, following liver damage and alteration of functional integrity in the kidney leading to proteinuria, so, their plasma level decreases in hepatotoxic/nephrotoxic conditions ( Sen et al., 2013 ).…”
Section: Discussionmentioning
confidence: 53%
See 3 more Smart Citations